A rare case of paragonimiasis miyazakii with lung involvement diagnosed 7 years after infection: A case report and literature review. Issue 5 (October 2015) - Yatera, Kazuhiro; Hanaka, Minako; Hanaka, Tetsuya; Yamasaki, Kei; Nishida, Chinatsu; Kawanami, Toshinori; Kawanami, Yukiko; Ishimoto, Hiroshi; Kanazawa, Tamotsu; Mukae, Hiroshi
Abstract We report a rare case of pulmonary paragonimiasis caused by Paragonimus miyazakii that showed pulmonary manifestations and a long-term clinical course after infection. A 45-year-old Japanese male developed cough and dyspnea in 2004 and was diagnosed with eosinophilic pneumonia. He had been treated with low-dose oral corticosteroid for 7 years. He recalled that he had consumed a large amount of raw freshwater crab (Geothelphusa dehaani) several weeks before he had been admitted for the first time, and that had been the only occasion when he had eaten this meat. The patient was referred to our hospital due to persistent hemoptysis, and his chest computed tomography scan showed pulmonary nodules and cavities, and his serum total IgE level was elevated. Bronchoscopy was performed, and ova were detected in the bronchoalveolar lavage fluid. The morphological examination of the ova and immunoserological examination yielded typical findings of P. miyazakii. Treatment with praziquantel improved his chest radiographic findings and a decrease of serum total IgE, as well as the values of immunoserological examination for P. miyazakii. The clinical course of this patient indicated that he had been infected with P. miyazakii for 7 years at least, which is unusual for paragonimiasis miyazakii.